Mixing and Crystal Scavenging in the Main Ethiopian Rift Revealed by Trace Element Systematics in Feldspars and Glasses. (11th January 2019) - Iddon, Fiona; Jackson, Charlotte; Hutchison, William; Fontijn, Karen; Pyle, David M.; Mather, Tamsin A.; Yirgu, Gezahegn; Edmonds, Marie
Abstract: For many magmatic systems, crystal compositions preserve a complex and protracted history, which may be largely decoupled from their carrier melts. The crystal cargo may hold clues to the physical distribution of melt and crystals in a magma reservoir and how magmas are assembled prior to eruptions. Here we present a geochemical study of a suite of samples from three peralkaline volcanoes in the Main Ethiopian Rift. While whole‐rock data show strong fractional crystallization signatures, the trace element systematics of feldspars, and their relationship to their host glasses, reveals complexity. Alkali feldspars, particularly those erupted during caldera‐forming episodes, have variable Ba concentrations, extending to high values that are not in equilibrium with the carrier liquids. Some of the feldspars are antecrysts, which we suggest are scavenged from a crystal‐rich mush. The antecrysts crystallized from a Ba‐enriched (more primitive) melt, before later entrainment into a Ba‐depleted residual liquid. Crystal‐melt segregation can occur on fast timescales in these magma reservoirs, owing to the low‐viscosity nature of peralkaline liquids. The separation of enough residual melt to feed a crystal‐poor postcaldera rhyolitic eruption may take as little as months to tens of years (much shorter than typical repose periods of 300–400 years). Our observations are consistent with these magmatic systems spending significant portions of their life cycle dominated by crystalline mushes containing ephemeral, small (< 1 km 3 ) segregations of melt. This interpretation helps to reconcile observations of high crustal electrical resistivity beneath Aluto, despite seismicity and ground deformation consistent with a magma body. Key Points: Alkali feldspars have variable trace element (Ba) concentrations, some far from equilibrium with their carrier liquids (melts) Some feldspars are antecrysts (in equilibrium with a liquid on the line of descent, but not the host melt), picked up from a crystal mush Ignimbrites erupted during caldera‐forming events are dominated by antecrysts, perhaps scavenged from deep parts of the magma reservoir